Playing at Being Mobile: Gaming and Cute Culture in South Korea - Hjorth, Larissa (Fibreculture Journal, 2006)
This paper is based on ongoing research into the gendered use of mobile convergent media in the Asia-Pacific region. In particular, what role does the cute have and how does it correlate with types of consumption? As a region, the Asia-Pacific is marked by diverse penetration rates, subject to local cultural and socio-economic nuances. Two defining locations - Seoul (South Korea) and Tokyo (Japan) - are seen as both mobile centres and gaming centres which the world looks towards as examples of the future-in-the-present. Unlike Japan, which pioneered the keitai (mobile) IT revolution with devices such as i-mode, South Korea has become a centre for mobile DMB (Digital Multimedia Broadband) with the successful implementation of TV mobile phones (TU mobile) in 2005. One of the key features of mobile media technologies is the attempt by the industry to find the next killer application . One such application is the possibility of online multiplayer games accessed through mobile (broadband) telephonic devices such as MMO golf RPG Shot Online (a golf game for mobile phones). Amongst this frenzy of trend spotting and stargazing, Seoul as a mobile broadband and gaming centre provides a curious case study for the social and cultural intricacies informing the rise of gaming as an everyday practice for many Koreans.This article begins by outlining the game play and technoculture particular to South Korea and then explores the phenomenon of Kart Rider in South Korean gaming cultures - and its perception/ reception outside Korea - to sketch some of the issues at stake in playing it cute (particularly in the form of cute avatars), consuming Korea and the endurance of co-present communities. In particular, it contemplates the implications of current emerging online mobile gaming genres such as so-called female games such as the cute' Kart Rider in order to think about changing modes of game play and attendant social spaces.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Autrice; _Nettoyé